ANALISIS TINGKAT KESEJAHTERAAN BURUH PERKEBUNAN KELAPA SAWIT PT.BATU MAS SEJAHTERA KECAMATAN SUNGAI LAUR KABUPATEN KETAPANG - Silvany, Pralinia; Matsum, Junaidi H.; Asriati, Nuraini (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This research was conducted in the people of Bengaras Village, Sungai Laur District, Ketapang Regency with the general aim of this research being to obtain information and find out about the welfare of oil palm plantation workers in Suangai Laur District, Ketapang Regency. This research uses a qualitative approach method, with a survey research type. Informants in this study used a purposive sampling technique with a total of 10 informants. Based on an analysis of the welfare of freelance daily workers on oil palm plantations PT. Batu Mas Sejahteran regarding the income received to meet daily needs is still far from sufficient, because there are often delays in paying salaries and the effective working days of casual daily workers per month are only 18 effective working days, with the monthly salary that casual daily workers receive is Rp. . 1,872,000,- or per day you only get Rp. 104,000,-. Meanwhile, the Ketapang Regency UMK level in 2023 is IDR. 3,100,000,-. So for the income of casual daily workers at PT. Batu Mas Sejahtera, Bengaras Village, Sungai Laur District is still low and still below the UMK of Ketapang Regency